Serial Analysis of the T-Cell Receptor β-Chain Repertoire in People Living With HIV Reveals Incomplete Recovery After Long-Term Antiretroviral Therapy - Towlerton, Andrea M. H.; Ravishankar, Shashidhar; Coffey, David G.; Puronen, Camille E.; Warren, Edus H. (Frontiers in Immunology, 2022)
Long-term antiretroviral therapy (ART) in people living with HIV (PLHIV) is associated with sustained increases in CD4+ T-cell count, but its effect on the peripheral blood T-cell repertoire has not been comprehensively evaluated. In this study, we performed serial profiling of the composition and diversity of the T-cellreceptor -chain (TRB) repertoire in 30 adults with HIV infection before and after the initiation of ART to define its long-term impact on the TRB repertoire. Serially acquired blood samples from 30 adults with HIV infection collected over a mean of 6 years (range, 1-12) years, with 1-4 samples collected before and 2-8 samples collected after the initiation of ART, were available for analysis. TRB repertoires were characterized via high-throughput sequencing of the TRB variable region performed on genomic DNA extracted from unsorted peripheral blood mononuclear cells. Additional laboratory and clinical metadata including serial measurements of HIV viral load and CD4+ T-cell count were available for all individuals in the cohort. A previously published control group of 189 TRB repertoires from peripheral blood samples of adult bone marrow transplant donors was evaluated for comparison. ART initiation in PLHIV was associated with a sustained reduction in viral load and a significant increase in TRB repertoire diversity. However, repertoire diversity in PLHIV remained significantly lower than in the control group even after long-term ART. The composition of TRB repertoires of PLHIV after ART also remained perturbed compared to the control cohort, as evidenced by large persistent private clonal expansions, reduced efficiency in the generation of TRB CDR3 amino acid sequences, and a narrower range of CDR3 lengths. Network analysis revealed an antigen-experienced structure in the TRB repertoire of PLHIV both before and after ART initiation that was quite distinct from the structure of control repertoires, with a slight shift toward a more naïve structure observed after ART initiation. Though we observe significant improvement in TRB repertoire diversity with durable viral suppression in PLHIV on long-term ART, the composition and structure of these repertoires remain significantly perturbed compared to the control cohort of adult bone marrow transplant donors.